Pengaruh Pembelajaran Kimia Melalui Inkuiri Terbimbing Dengan Pendekatan Saintifik Terhadap Hasil Belajar Dan Sikap Ilmiah Siswa Kelas X SMA Negeri 9 Palu - Alamsyah Alamsyah; Baharuddin Hamzah; Solfarina Solfarina (Mitra Sains, 2015)
It has been conducted a research where that aim is to describe the influence of the guided inquiry learning process with the scientific approach on the learning outcomes of and scientific attitudes of student. The population in this study is all students of class X SMA Negeri 9 Palu with academic year 2014/2015. The purposive sampling is used for sampling technique where class XA as an experimental class and class B as a control class. The research design used is the pretest-posttest control group design. Statistical test used is the Mann-Whitney U-Test. Based on the analysis of the calculation of the value of <g>, there is an improvement on learning outcomes of student in the experimental class compared to the control class. Based on statistical test, it is showed that Zcalculation<Ztable at significant level of 0.05, which means that the guided inquiry in chemistry learning through scientific approach gives a significant effect on learning outcomes and scientific attitudes of student in class X SMA Negeri 9 Palu on electrolyte and on-electrolytes solution topic.